Learning styles of endodontics students at a private university in southern Brazil - Kublitski, Prescila Mota de Oliveira; Tomazinho, Paulo Henrique; Tomazinho, Flávia Sens Fagundes; Brancher, João Armando; Leonardi, Denise Piotto; Gabardo, Marilisa Carneiro Leão (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The learning styles of Endodontics students from an undergraduate Dentistry course were evaluated using the Felder-Soloman Learning Styles Index. 144 students participated, from the morning and night shifts, between May and June 2016. Of these, 80.6% were female and 68.5% of the morning shift. The average age was 22.94 years and the median grade in the discipline was 6.52. The predominant styles were sensory, visual, active and sequential, respectively. The correlation between age and shift, and the intensity of each learning style had no statistically significant difference (p ˃ 0.05). Women were more sensory and men more visual (p = 0.010). In the correlation between the annual average and the styles, there was a significant difference for the sensory and the intuitive (p <0.001). Most had a mixed preference between learning styles, regardless of the shift.